Sleep disturbances and childhood cancer - A tertiary care experience - Prakruthi Kaushik; Sujata Sharma; Nikita Shah; Purvi Kadakia Kutty; Radha Ghildiyal (Elsevier, 2022)
Introduction: Sleep is essential for physical and mental well being. Cancer and its therapy affect sleep which adds on to the burden of healthy living. Various studies have shown that disturbed sleep patterns have a bearing on the quality of life. Objective: To determine the incidence of abnormal sleep patterns and study its associations with treatment for cancer in children. Materials and methods: This cross-sectional study was conducted at a tertiary health-care centre of a metropolitan city in Western India from January to March 2017. Sleep was assessed in children between age group 3-15 years undergoing therapy for cancer using BEARS screening tool and the Children's Sleep Habits Questionnaire (CSHQ). Questions were administered to parents/guardians accompanying the child. Results: A total of 63 children were included. The prevalence of sleep disturbance as assessed by CSHQ score was 69.8%. On BEARS screening 38(60%), reported a problem with sleep. Presence of parents had a positive impact on sleep. The mean CSHQ scores of the 25 children who had no parent reported was 46.2 and 20 of them had scores more than 41. The sleep domains significantly affected in these children were Bedtime Resistance, Sleep duration, Sleep anxiety, Night Awakenings, Parasomnia and Fatigue. Conclusion: Evaluation for the cause of sleep problems and interventions to address these issues is necessary for better care of these children. Further studies on impact of sleep disturbances on outcomes of cancer therapy and quality of life are the need of the hour.